2012
DOI: 10.1080/08824096.2012.684808
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Comparative Cancer Risk and Cancer Efficacy Perceptions on Cancer-Related Information Seeking and Scanning Behaviors

Abstract: This study examined the interaction between perceived cancer risk and self-efficacy related to cancer screening on cancer-related information seeking and scanning behaviors (SSB) among the general population. Individuals completed a cross-sectional survey, were classified into 1 of 4 clusters based on their relative risk and self-efficacy belief scores (i.e., high relative risk and high self-efficacy, high relative risk and low self-efficacy, low relative risk and high self-efficacy, and low relative risk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…As breast cancer is an illness with severe health consequences, women with a higher risk perception tend to seek out and pay attention to breast cancer content shown in the media (Nan, Underhill, Jiang, Shen, & Kuch, 2012;Rimal, 2010;Wong, 2012). Past research has shown that risk perception has a significant moderate association with seeking breast cancer information in the media (β = .37, p < .001; Nan et al, 2012).…”
Section: Risk Perception As a Motivator Of Media Attention And Interpmentioning
confidence: 90%
“…As breast cancer is an illness with severe health consequences, women with a higher risk perception tend to seek out and pay attention to breast cancer content shown in the media (Nan, Underhill, Jiang, Shen, & Kuch, 2012;Rimal, 2010;Wong, 2012). Past research has shown that risk perception has a significant moderate association with seeking breast cancer information in the media (β = .37, p < .001; Nan et al, 2012).…”
Section: Risk Perception As a Motivator Of Media Attention And Interpmentioning
confidence: 90%
“…Information seeking refers to actively and deliberately searching for and gathering information from the media, interpersonal conversation, the Internet, medical providers, or other information sources that are outside of the normal flow of conversation (Niederdeppe et al, 2007; Powe, 2015; Wong, 2012). This is different from information scanning , which refers to passively encountering information or being exposed to information unintentionally (Lee, Zhao, & Pena, 2016; Shim, Kelly, & Hornik, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of cancer patients (74-98%) report that they want as much information as possible about their condition, but the percentage who actually seek cancer information appears to be dependent on factors unrelated to their diagnosis (Rutten et al, 2005;Chen & Sui, 2001;Foltz & Sullivan, 1996). These variables may include demographics, exposure to a friend or family member with cancer (Carlsson, 2009;Czaja et al, 2003;Rees & Bath, 2001), or their perceived risk of developing ovarian cancer in their lifetime (Wong, 2012;Weaver et al, 2010;Kaphingst et al, 2009;Roach et al, 2009).…”
Section: The Online Information Seeking Behaviors Of Individuals At Rmentioning
confidence: 99%
“…Perceived risk may be affected by any number of variables, including genetic risk information (Aspinwall et al, 2014). For example, receiving a positive genetic test may increase an otherwise healthy individual's perception of risk, and impact their motivation to seek information (Wong, 2012). That individual may be more or less inclined to access, consume, or trust certain online sources of health information (Aspinwall et al, 2015;Wong, 2012).…”
Section: The Online Information Seeking Behaviors Of Individuals At Rmentioning
confidence: 99%
See 1 more Smart Citation